Analysis of Students Problem-Solving Ability in Economics PBL at SMAN Sumber Harta Viewed from Learning Styles - Juwarni, Juwarni; Hilyati Milla; Merri Sri Hartati (Tinta Emas Institute, 2025)
This study aims to evaluate students ability to solve problems in Economics subjects at SMAN Sumber Harta which is influenced by learning styles with the use of Problem Based Learning (PBL) models. The method applied was qualitative descriptive with the research subjects of 20 students in class X.2 selected by purposive sampling based on the learning style identified through the Visual-Auditory-Kinesthetic (VAK) questionnaire. This study found that in understanding the problem, all learning styles showed the same ability in each given problem, in planning and implementing problem solving, auditory and kinesthetic learning styles dominated, while visual learning styles were less than optimal. In the re-checking activity, there is no learning style that is able to carry out this step well. Overall, auditory learning styles are superior in structuring and executing problem-solving over visual and kinesthetic learning styles. This research makes a significant contribution in understanding that students' learning styles can affect problem-solving skills in PBL-based learning.